MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF AL-QUR’AN DAN AS-SUNNAH - Nashiratunnisa, Nashiratunnisa; Anwar, Cecep (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
Islamic education is becoming more prevalent throughout society and is in high demand due to its perceived academic and Qur'an memorization advantages. In addition to strong management, good education is attained through good administration. According to the Qur'anic verses, management already exists and is illustrated by the Prophets and Apostles of his day. Therefore, the purpose of this article is to study and describe educational management from the Qur'an and Sunnah's perspective. There are numerous verses in the Qur'an that discuss school management, particularly the four educational responsibilities of Planning, Organizing, Acting, and Controlling (POAC). Some verses can be understood quickly to be explanations of managerial functions, while others require the reader to have advanced cognitive abilities (HOTS). The history of the Prophet Muhammad saw is likewise heavily influenced by the four managerial functions. Therefore, it may be stated that Islam had management science in the Qur'an and was exhibited by the Prophet Muhammad saw before Europeans were aware of it.